1998
DOI: 10.1111/j.1471-0528.1998.tb09347.x
|View full text |Cite
|
Sign up to set email alerts
|

Does sweeping of the membranes reduce the need for formal induction of labour? A randomized controlled trial

Abstract: Objective 1. To evaluate the effectiveness of sweeping of the membranes to reduce the need for a formal Design A randomised controlled clinical trial.Setting Three tertiary care hospitals of the province of Quebec, Canada.Population Two hundred women for whom non-urgent induction of labour was medically indicated.Methods Women were randomly allocated to sweeping of membranes, or vaginal examination for Bishop scoring only.Main outcome measures 1. Cumulative incidence and relative risk of induction of labour by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 15 publications
5
22
2
Order By: Relevance
“…10 Reported adverse effects of misoprostol, such as vomiting, diarrhoea, tachysystole or hyperstimulation, were not recorded in this study, possibly because of the single low dose administered. However, 20% of all the patients (in Stripping group and stripping along with Misoprostol group) reported that the procedure was uncomfortable and/or painful, similar to earlier reports, 15,20 and 6% had minimal spotting after the procedure, which subsequently subsided. No case of rupture of the membranes or antepartum haemorrhage was recorded.…”
Section: Resultssupporting
confidence: 66%
“…10 Reported adverse effects of misoprostol, such as vomiting, diarrhoea, tachysystole or hyperstimulation, were not recorded in this study, possibly because of the single low dose administered. However, 20% of all the patients (in Stripping group and stripping along with Misoprostol group) reported that the procedure was uncomfortable and/or painful, similar to earlier reports, 15,20 and 6% had minimal spotting after the procedure, which subsequently subsided. No case of rupture of the membranes or antepartum haemorrhage was recorded.…”
Section: Resultssupporting
confidence: 66%
“…In addition, to avoid interference with obstetric indications for induction of labour before 42 weeks, we evaluated sweeping in a low-risk population in a primary care setting. A major difference with most trials, in which sweeping was performed by one or two obstetricians, was the participation of many different midwives, 30 implying that our results reflect real practice. We also followed the suggestion of a strategy of multiple successive sweeping 10,18 rather than a single intervention.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, several studies reported the effectiveness of sweeping of the fetal membranes in reducing the incidence of prolonged pregnancies and the length of term gestations [5,6,12,13]. On the contrary, other authors reported that sweeping of the fetal membranes does not significantly increase the proportion of women who begin spontaneous labor [4,7,13,14].…”
Section: Discussionmentioning
confidence: 89%